Impairment of the Glymphatic Pathway and Putative Meningeal Lymphatic Vessels in the Aging Human. Issue 3 (30th January 2020) - Zhou, Ying; Cai, Jinsong; Zhang, Wenhua; Gong, Xiaoxian; Yan, Shenqiang; Zhang, Kemeng; Luo, Zhongyu; Sun, Jianzhong; Jiang, Quan; Lou, Min
Abstract : Objective: Aging is a major risk factor for numerous neurological disorders, and the mechanisms underlying brain aging remain elusive. Recent animal studies demonstrated a tight relationship between impairment of the glymphatic pathway, meningeal lymphatic vessels, and aging. However, the relationship in the human brain remains uncertain. Methods: In this observational cohort study, patients underwent magnetic resonance imaging before and at multiple time points after intrathecal administration of a contrast agent. Head T1‐weighted imaging was performed to assess the function of the glymphatic pathway and head high‐resolution T2–fluid attenuated inversion recovery imaging to visualize putative meningeal lymphatic vessels (pMLVs). We measured the signal unit ratio (SUR) of 6 locations in the glymphatic pathway and pMLVs, defined the percentage change in SUR from baseline to 39 hours as the clearance of the glymphatic pathway and pMLVs, and then analyzed their relationships with aging. Results: In all patients (N = 35), the SUR of the glymphatic pathway and pMLVs changed significantly after intrathecal injection of the contrast agent. The clearance of both the glymphatic pathway and pMLVs was related to aging (all p < 0.05). The clearance of pMLVs was significantly related to the clearance of the glymphatic pathway (all p < 0.05), and the clearance of the glymphatic pathway was significantly faster in patients with early filling of pMLVs than those with late filling (all p < 0.05). Interpretation: We revealed that both the glymphatic pathway and pMLVs might be impaired in the aging human brain through the novel, clinically available method to simultaneously visualize their clearance. Our findings also support that in humans, pMLVs are the downstream of the glymphatic pathway. Ann Neurol 2020;87:357–369